Highlights of the Clinical Pharmacy Congress 2018. Issue 8 (20th August 2018) - David, Felix
Abstract : Optimising COPD management, tackling hypoglycaemia in diabetes and NHS England's Medicines Value Programme were among the topics discussed at Clinical Pharmacy Congress 2018 held in London in April. This article provides an overview of some of the presentations.